Geomembrane factory and field thermally welded seams comparison. Issue 4 (August 2020) - Stark, T.D.; Hernandez, M.A.; Rohe, D.S.
Abstract: This technical paper presents a unique comparison of geomembrane factory and field welded thermal seams for a large off-stream water reservoir project. The results of the comparison show that factory welded seams exhibit higher seam peel and shear strengths at yield, less variability, and more consistency than field welded thermal seams. In particular, the results show that factory seams are about 10% stronger than field seams in shear and about 9% stronger in peel strength at yield. More importantly, this resulted in 100% of the factory welded seams passing the project seam strength requirements even though the factory welding speed was 1.1–1.6 times faster than the field welding speed. Conversely, about 25% of the field welded seams did not pass the initial specified field seam shear strength requirement, which caused significant delays, scheduling, and other construction issues. As a result, the field seam shear strength requirement was reduced from 9.6 kN/m to 8.2 kN/m to increase the number of field seams that achieved project requirements. Because the geomembrane was primarily factory fabricated, there were about 78% less field seams on this project than if the geomembrane was entirely field fabricated.